Morphological Investigation of Calcium Carbonate during Ammonification-Carbonization Process of Low Concentration Calcium Solution. (2nd September 2014) - Cheng, Huaigang; Zhang, Xiaoxi; Song, Huiping
Abstract : Ultrafine calcium carbonate is a widely used cheap additive. The research is conducted in low degree supersaturation solution in order to study the polymorphic phases' change and its factors of the calcium carbonate precipitate in the ammonification-carbonization process of the solution with calcium. Fine particles of calcium carbonate are made in the solution containing 0.015 mol/L of Ca 2+ . Over 98% of the calcium carbonate precipitate without ammonification resembles the morphology of calcite, while the introduction of ammonia can benefit the formation of vaterite. It was inferred that the main cause should be serious partial oversaturation or steric effects. Ammonia also helps to form the twin spherical calcium carbonate. However, particles formed in the process of ammonification-carbonization in solution with low concentration degree of calcium are not even with a scale of the particle diameter from 5 to 12 μ m. Inorganic salts, alcohol, or organic acid salts have significant controlling effect on the particle diameter of calcium carbonate and can help to decrease the particle diameter to about 3 μ m. Anionic surfactants can prevent the conglobation of calcium carbonate particles and shrink its diameter to 500 nm–1 μ m.